Primary care referral to multidisciplinary high risk foot services – too few, too late. Issue 1 (December 2015) - Plusch, D; Penkala, S; Dickson, HG; Malone, M
Abstract Background To determine if patients with no contact with a multi-disciplinary team High Risk Foot Service (MDT-HRFS) had an increased rate of hospital admission for diabetes foot infection compared to patients with contact. Secondary aims were to report on clinical outcomes. Methods A retrospective study was conducted at a major tertiary referral hospital in metropolitan Sydney over 12 months. An ICD-10 search of the electronic medical record system and paper medical charts identified patients with diabetes mellitus (type 1 or type 2) and a primary admission for diabetes foot infection (DFI). Patients were categorised as having contact or no contact with an MDT-HRFS. Results One hundred ninety-six hospital admissions (156 patients) were identified with DFI over a 12-month period. Patients with no contact with a MDT-HRFS represented three quarters of admissions (no contact = 116, 74.7 % vs. contact = 40, 25.6 %, p = 0.0001) and presented with more severe infection (no contact = 39 vs. contact = 12). The odds of lower extremity amputation increased five-fold when both no contact and severe infection occurred in combination (no contact with severe infection and amputation = 34, 82.9 % vs. contact with severe infection and amputation = 7, 17.1 %, OR 4.9, 95 % CI 1.1–21.4, p = 0.037). Using estimates of both the contact and no contact population of people with diabetes and high-risk feet and assuming the risk of amputation was the same, than the number of expected amputations in the no contact group should have been 55, however the observed number was 77, 22 more than expected (p = 0.0001). Conclusions Patients with no contact with a MDT-HRFS represented the majority of admissions for DFIs to a tertiary referral hospital. This group on population estimates appears to be at high risk of amputation of the lower extremity and therefore early referral of this high-risk group might lower this risk.